Leadership, Incentives, and Motivation for Customer Care Performance in Automotive Service Organizations - Harun Nurrosyid; Deti Mulyo Harsono; Sapta Dwikardana (Goodwood Publishing, 2026)
Purpose: This study aims to analyze the relationship between leadership style, incentives, and work motivation on the performance of customer care employees in carrying out follow-up reminder service activities at Honda car dealers in the Jabodetabek region Research Methodology: This research was conducted at Honda car dealers in the Jabodetabek area using a quantitative explanatory research design. Data were collected using a Likert-scale questionnaire distributed via Google Forms to 62 customer care employees selected using purposive sampling. The study applied multiple linear regression analysis to examine the partial and simultaneous relationships among the variables. Instrument validity and reliability tests were performed, along with classical assumption tests, including normality, multicollinearity, and heteroscedasticity. Data analysis was conducted using a statistical software. Results: Leadership style, incentives, and work motivation were significantly related to customer care performance in follow-up reminder service activities, both individually and simultaneously. Work motivation showed the strongest relationship with employee performance among the variables. Conclusions: Employee performance in follow-up reminder service activities is influenced by internal organizational factors, particularly leadership style, incentive systems, and motivation. Limitations: This study is limited to one brand, one region, and a limited number of variables, which may restrict the generalizability of its findings. Contributions: This study contributes empirically to the human resource management and service management literature by contextualizing employee performance within follow-up reminder service activities and providing practical insights for automotive dealer management.